The Effect of Plyometric Training Performed on Different Surfaces on Some Performance Parameters - Gencer, Yildirim Gokhan; Buga, Selim (Progress in Nutrition, 2022)
Study Objective: This study aimed to examine the effects of plyometric training performed on different surfaces on some performance measurement parameters in basketball players and compare them. Methods: Experimental design with the pretest-posttest control group, which was one of the real experimental models, was used in the study. Using simple random sampling, one of the random sampling methods, 48 ​​male basketball players were divided into aqua (n=12), grass surface (n=12), parquet surface (n=12), and control groups (n=12). In the study, after the plyometric training, on-court basketball technical training was applied to the experimental groups. On the other hand, only basketball technical training was applied to the control group. Height, body weight, vertical jump, long jump, balance, agility, flexibility, speed, and anaerobic power measurements were taken before and after the training. Results: In the pre-test and post-test comparisons within the group, the difference was significant in balance and sprint measurement, except for the control group, in the aqua group in the flexibility measurement tests, in all groups in the vertical jump and long jump measurements, and in the aqua, grass and parquet surface groups in the agility measurement (p<0,05) was found and it was determined that the best improvement was in favor of the group working in water. Conclusions: As a result, it can be said that plyometric exercises applied in aqua, grass, and parquet surfaces will positively improve the vertical jump strength, agility, balance skills, long jump, and anaerobic power performance of 12-15 age-group basketball players.